1996
DOI: 10.21236/ada381505
|View full text |Cite
|
Sign up to set email alerts
|

Blind Separation of Event-Related Brain Responses into Independent Components

Abstract: Functional imaging of brain activity based on changes in blood flow does not supply information about the relative timing of brief bursts of neural activity in different brain areas 1 ' 2 . Multichannel electric or magnetic recordings from the scalp provide high temporal resolution, but are not easily decomposed into the separate activities of multiple brain networks.We report here a method for the blind separation of event-related brain responses into spatially stationary and temporally independent subcompone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…1B). Principal components of data generated by temporally sparse and independent, but spatially nonorthogonal, sources will be linear combinations of activity in all the sources, whereas ICA components of the data will individually identify the larger sources (28). The proposed Varimax extension of the PCA method rotates the PCA vectors to maximize the variance of their activation waveforms (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Principal components of data generated by temporally sparse and independent, but spatially nonorthogonal, sources will be linear combinations of activity in all the sources, whereas ICA components of the data will individually identify the larger sources (28). The proposed Varimax extension of the PCA method rotates the PCA vectors to maximize the variance of their activation waveforms (4).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the strengths and limitations of the method, we ran a number of numerical simulations in which 600-point signals recorded from the cortex of a patient during preparation for operation for epilepsy were projected to simulated scalp electrodes through a three-shell spherical model (28,29). We used electrocorticographic data in these simulations as a plausible best approximation to the temporal dynamics of the unknown ERP brain generators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Error and no-response trials were excluded from analyses. Independent component analysis (19) was used to correct for eyeblink artifacts. Corrected single-trial epochs were rereferenced to averaged mastoids.…”
Section: Subjectsmentioning
confidence: 99%
“…The method developed, termed iterative ICA (iICA), is an iterative implementation of the information maximization algorithm originally proposed by Makeig et al [6]. We have shown that iICA can provide estimates of a particular EP component out of an entire waveform, and this EP component is made clearly visible in each single trial [4,15].Thus, the method allows studying the dynamic evolution of the cortical generators that give rise to speci c EP components.…”
Section: Introductionmentioning
confidence: 99%